Accounting Comparability and Its Effect on Investment Efficiency - MohammadAli Aghaei (Ph.D) (Shahid Bahonar University of Kerman, 2018)
The purpose of this study is to evaluate the impact of accounting comparability on investment efficiency. When a firm has greater accounting comparability with industry peer firms it facilitates that firm’s learning from peer firm investments leading to better investments by the subject firm. Therefore, we expect firms with greater accounting comparability, have higher investment efficiency. Using regression analysis, the relationship between these variables was investigated in 166 companies listed on Tehran Stock Exchange for the period 2008 to 2015. Evidence of research shows that there is a positive and significant relationship between accounting comparability and investment efficiency. In other words, accounting comparability increases the amount of access to accounting information about investment projects, and leads to improved investment decisions.